Profil level penalaran geometris siswa SMP dalam menyelesaikan soal geometri berdasarkan Teori Van Hiele - Riera, Ecin; Utami, Anita Dewi; Darmawan, Puguh (UNIVERSITAS NEGERI MALANG, 2022)
This study aims to describe the level profile of junior high school students' geometric reasoning in solving geometry problems in terms of Van Hiele's theory. The instruments used in this study consisted of the main and supporting instruments. The main instrument is the researcher himself. The supporting instruments consist of a Van Hiele thinking level test, a geometry problem-solving test and an interview guide that aims to verify how students step in solving geometry problems. The results showed that most students were still low in mastering the subject of understanding the concept of geometry so that it could cause errors when answering questions. This shows that the mathematical reasoning of junior high school students based on Van Hiele's theory for subjects with high and medium abilities is at level 1 (analysis) while those with low abilities are at level 0 (visualization).